Jejak Pembinaan Religi Mahasiswi STIBA Makassar Berbasis Al-Qur’an di Desa Moncongloe Kecamatan Moncongloe Kabupaten Maros - Nuraeni Novira (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2023)
The objective of the STIBA Makassar Community Service Program Batch VI in Moncongloe Village is to realize community service which is a pillar of the Tri Dharma of Higher Education. The method of implementing this activity is to first map the problems and needs using the SOAR analysis instrument. After analyzing the problems and needs, a work program is prepared according to the needs of the community. The work programs that have been successfully implemented are Teaching TPA/TPQ, Teaching Arabic for Children, Clean Friday and Community Service and Tablig Akbar Welcoming the Month of Ramadan. All of these programs this work has been implemented and shows good initial results and will be continued by MWC Moncongloe Maros district.